2015
DOI: 10.1097/apo.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional Outcomes of Pars Plana Vitrectomy for Lamellar Macular Defects

Abstract: Pars plana vitrectomy provided a high success rate of anatomical and functional improvement for eyes with all types of lamellar macular defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A correlation between a low MFT and poor preoperative VA has been detected in a study by Holland 1 on 89 eyes. The observation of patients with relatively well-preserved VA and MFT will thus be followed and observed according to current procedures.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…A correlation between a low MFT and poor preoperative VA has been detected in a study by Holland 1 on 89 eyes. The observation of patients with relatively well-preserved VA and MFT will thus be followed and observed according to current procedures.…”
Section: Discussionmentioning
confidence: 83%
“…The observation of patients with relatively well-preserved VA and MFT will thus be followed and observed according to current procedures. On the contrary, Holland et al 1 also found a significant correlation between the level of pre- and post-operative VA: the better preoperative VA, the better the postoperative VA gets. In such cases, it will be beneficial to perform PPV on the majority of these patients, to ensure the VA improves as much as possible.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations